Pengaruh Video Edukasi Berbahasa Banjar terhadap Pengetahuan dan Sikap terkait Antibiotik pada Perempuan - Intannia, Difa; Lingga, Herningtyas Nautika (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
Inappropriate use of antibiotics due to lack of understanding and public knowledge is one of the causes of antibiotic resistance. Providing education via video to the public is a strategy that can be used to increase knowledge about the use of antibiotics. This study aims to assess the effect of providing local language educational videos about antibiotics and their use on increasing the knowledge and attitudes of women living in the Banjar Regency area, South Kalimantan. This research is Quasi-experimental research with a pretest posttest intervention with a control group research design using a purposive sampling technique and an intervention in the form of educational videos in the Banjar language. A valid and reliable questionnaire was used to assess knowledge and behavior in using antibiotics. Analysis of changes in knowledge and behavior scores between the control and intervention groups was carried out with the Mann-Whitney test. The number of respondents involved in the study was 80 women who were divided into a control group (40 people) and an intervention group (40 people). The results showed that the average pre-test and post-test knowledge scores in the control group (7.58 ± 1.81 and 7.85 ± 2.11) and the intervention group (7.33 ± 2.30 and 8.78 ± 2.93) with a significance value of p = 0.026. The mean scores of pre-test and post-test behavior in the control group (6.03 ± 2.60 and 6.15 ± 2.70) and the intervention group (6.33 ± 2.37 and 7.50 ± 2.05) with a significance value of p = 0.016. It can be concluded that providing educational videos in Banjar language can increase Females knowledge and behavior in using antibiotics in Banjar Regency.